Inferring potential causative microbial factors of intestinal atrophic disease in the sea cucumber Apostichopus japonicus - Yu, Juanwen; Sawabe, Tomoo; Yamano, Ryota; Koike, Shotaro; Sakai, Yuichi; Mino, Sayaka (Frontiers in Marine Science, 2023)
The overexploitation of the wild populations of Apostichopus japonicus has caused a significant decline in their numbers, prompting the establishment of a sea cucumber aquaculture industry that has become a major player in East Asia. Recent research has focused on identifying the various factors that may affect sea cucumber aquaculture, including water quality, diet, and the microbiome associated with their hosts. Notably, studies on host-associated microbiomes have emerged as a prominent area of research, particularly in the context of investigating the relationship of the microbiome with diseases that have caused significant economic losses. Intestinal atrophy of A. japonicus larvae has been reported at a number of sea cucumber farms in Japan, but there have been no factor screenings, and there is currently no efficient mitigation. In this study, we applied metagenomic analyses for the first time to an intestinal atrophic case of the sea cucumber A. japonicus larvae, which occurred in an aquaculture facility in Hokkaido, Japan, elucidating potential causative microbial factors and comparing the diseased microbiome against the healthy pan-microbiome. Through our metagenome comparisons, we have found significant increases in Oceanicoccus, Ruegeria, Nioella, Labrenzia, Tenacibaculum, and Muricauda in the diseased larvae. Among those, Tenacibaculum was estimated to potentially be the most pathogenic bacterium in the development of intestinal atrophic disease due to previous outbreaks of sea urchin diseases in the same facility. Our metagenomic approach demonstrates the further need of microbial screening of such causative agents and identification of the pathogenesis of such diseases, which could contribute to establishing more sustainable aquaculture in the sea cucumber industry.